Tuo Dolphins - Scott, Rolf Erik; Crawford, Peter Ian (Journal of Anthropological Films, 2023)
Tuo Dolphins takes place in both Aarhus, Denmark and in the Reef islands, the Solomon Islands. Moffat Bonunga, visits the Danish anthropologists Jens Pinholt and Peter I. Crawford in Aarhus to help them with their work on the film project. This included talking about a special event when dolphins ran ashore at Tuo village. The people of Tuo have a mythical relationship with dolphins, covered by a traditional so-called kastom story, the incident confirming the fascinating relationship between the dolphins landing on the beach and the kinship relationships. The phenomenon had allegedly been triggered when a member of a specific family line, Pelewe, passed away a few weeks before. The villagers decided to re-enact part of their Dolphin story to capture it on film, thereby using the film, and its crew, to both present and confirm the truthfulness of the legend and myth.